'There wasn't all that much to do … at least not here': memories of growing up in rural south-west England in the early twentieth century. Issue 2 (October 2020) - Harrison, Laura
Abstract: Stan was born in 1911 in a small village near the north Somerset coast. When recalling his life in the countryside, he felt that 'there wasn't much to do in the evenings … at least not here'. Drawing upon evidence from personal accounts of growing up in the south-west of England in the early twentieth century, this article examines memories of youth in the countryside, with a particular focus on the leisure lives of young people and their experiences of rural space and place. In addition to adding to our knowledge on the lives of rural youth, this study also provides new insights into the complex relationship between people and their environment, and has implications for our understandings of the early formation of a distinct youthful identity in England. The countryside was not simply a backdrop in these recollections; rather, it was formative in how those that grew up in rural communities understood their experience of being young.